(untitled) (ESMAT Magazine, 2025)
The article analyses the judicialization of the 2023 and 2024 Selection Processes at the Federal University of Amapá (UNIFAP), based on the legal and hermeneutical controversies generated by Resolution no. 21/2022, which redefined the institution's vacancy reservation policy. The research, which is descriptive and qualitative- quantitative in nature, is based on a documentary analysis of 43 court cases extracted from the PJe system, covering the period from January 2023 to December 2024. The results show that conflicting judicial decisions directly affected the enrollment of candidates, causing successive changes to the public notice and generating institutional instability. The research highlights the insufficiency of the formalist reading of the law, predominant in some of the decisions, and proposes black and anti-discriminatory hermeneutics as an alternative theoretical framework capable of highlighting the impact of the social position of legal interpreters on the application of affirmative action. The conclusion is that the absence of an inclusive vision contributes to the reproduction of structural asymmetries and that it is necessary to rethink the limits of judicial intervention in public education policies. As a practical recommendation, we propose the creation of training programs for the judiciary in partnership with public universities, especially federal universities, with a view to critical training in race relations, legal-racial literacy and overcoming the ideology of the myth of racial democracy, with a viewmaking law an instrument of substantive justice and social emancipation.